The Effect of ERM Disclosure on Firm Performance and Firm Value in the Energy Sector Listed on the Indonesia Stock Exchange - Mulyadi Mulyadi; Dewi Hanggraeni (Journal of Management, Economic, and Accounting, 2026)
This study investigates the relationship between Enterprise Risk Management (ERM) disclosure, firm performance, and firm value in energy sector companies listed on the Indonesia Stock Exchange. The energy sector provides a relevant context because firms in this industry are exposed to operational, commodity price, regulatory, environmental, financing, and energy transition risks. Firm performance is measured by Return on Assets (ROA), while firm value is measured by Tobin’s Q. The study employs panel data from 31 energy sector companies during the 2021–2025 period, resulting in 155 firm-year observations. ERM disclosure is measured using a disclosure index based on 20 items derived from the COSO ERM Framework 2017. The empirical analysis applies panel data regression using a Fixed Effects Model with standard errors clustered by firm. The findings reveal that ERM disclosure has a negative and significant effect on ROA. This result suggests that broader ERM disclosure in the energy sector does not necessarily indicate higher profitability, but may reflect greater risk complexity and higher risk management costs borne by firms. In contrast, ERM disclosure has a positive but insignificant effect on Tobin’s Q, indicating that market valuation is not primarily driven by the extent of ERM disclosure. Investors appear to place greater emphasis on actual profitability, capital structure, cash flow prospects, commodity price dynamics, and energy transition risks. These findings imply that ERM disclosure should focus on the quality and effectiveness of risk management practices rather than merely increasing the volume of information disclosed in annual reports.